Climate Change and Air Pollution Effects on Forest Ecosystems - Badea, Ovidiu; De Marco, Alessandra; Sicard, Pierre; Tanase, Mihai A. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Both climate change and air pollution have large negative impacts on physiological processes and functions at the individual tree level and on whole forest ecosystems. The objective of climate change and air quality monitoring is to make decisions, based on scientific knowledge, regarding how to best manage and improve the current state of the environment. Our ability to take urgent measures to combat climate change and its impact on forest ecosystems and conserve forest biodiversity depends upon our knowledge of the latest scientific results on the status of forest ecosystems. Unfortunately, there are a lot of gaps in our knowledge of the detection and monitoring of their effects on forest ecosystems. This book presents relevant results from scientific research in the fields of climate change, air pollution, forest conservation, protection and monitoring that can contribute to a better science-policy interaction and to the elaboration of specific strategies, in accordance with the areas of forest sciences from IUFRO RG 8.04.00 - Impacts of air pollution and climate change on forest ecosystems.